Analisis Jaringan FTTH (Fiber To The Home) Di Perumahan Maton House, Pekanbaru - Andreas Andreas; Ery Safrianti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Maton House housing has a local fiber access network that uses a duct system and the device feeder are inefficiency. This papper purpose to analyzes the FTTH network at Maton House-Pekanbaru Housing to improve the efficiency of optical transmission, using several parameters such as: power budget link, rise time budget, and optical power. The analysis process is done with some supporting software such as: Optisystem, AutoCad, and Google Earth. Calculation of Optical Power analysis parameters performed by simulation using Optisystem software found the average value of loss is 21.11 and the measurement using Opical Power Meter found the average loss value is 22.50 dBm. According to the acquisition of large optical power on optical transmission in Maton House housing proves the network is much smaller of damping than the standard total that is below -28 dBm based on IEEE at 802.8 .Keywords: FTTH, link power budget, rise time budget, optical power.